Collaborative mixed reality environments: an application for civil engineering - Capra, Mauricio (2010)
The present thesis designs, implements and evaluates a channel for interaction between office and field users through a collaborative mixed reality system. This channel is aimed to be used for civil engineering purposes and is thus oriented toward the design and construction phases. Its application should contribute to the reduction of the challenges faced by those involved in a civil engineering project dealing with communication, collaboration and mutual understanding. Such challenges can become real problems for multidisciplinary teams of architects, engineers and constructors when working on the same project. In the context of this thesis, outdoor users are equipped with a real-time kinematic global positioning system receiver, a notebook, a head-mounted display, a tilt sensor and a compass. A virtual environment representing components of a civil engineering project is displayed before their eyes. Outdoor users share this collaborative virtual environment with indoor ones. They can talk to and see each other through an avatar. Indoor users can take part from any location where Internet is available. The goal of this thesis is to show that a networked solution of at least two users (In this case, indoor and outdoor users) is an opportunity for outdoor users to perform complex tasks whilst experiencing an immersive augmented reality application. Indoor users interact with outdoor ones when handling and navigating the virtual environment, guiding their counterpart through the scene and making clear common points of understanding. The thesis evaluates how users interact within a prototype system using a formative approach. Users are introduced to the system and motivated to “talk loudly”, thus verbalising what they are experiencing during the tests. All users are video-recorded while performing the exercises and interviewed immediately after. The evaluation reveals that users end up experiencing a system that is too immersive, which ends up narrowing their “attentional spotlight” to the virtual environment and not, as desired, experiencing an augmented reality system. The evaluation also makes clear that the design of the virtual environment is eventually more important for users than the system itself, and it is completely the kind of application that it is being used to and who the users are.